ANALISIS KURVA PHILLIPS DAN HUKUM OKUN DI INDONESIA TAHUN 1986-2016 - Prihartini Budi Astuti (P4M STIE Putra Bangsa, 2016)
This study aims to determine the fit between Phillips Curve theory and Okun's law with the economic conditions that occurred in Indonesia in 1986-2016. This research is a descriptive quantitative research. Data used in the study is rate of economic growth, the unemployment rate and the inflation rate in Indonesia in 1986-2016. The data was taken from the website of Bank Indonesia and Badan Pusat Statistik. Quantitative analysis method used is correlation analysis. The analysis showed that there was no agreement between Phillips Curve theory and Okun's law with the economic conditions that occurred in Indonesia in 1986-2016. Phillip curves for compliance with the conditions of the Indonesian economy in 1986-2016, from data analysis obtained correlation coefficient of -0.16 with significance value of 0.931. From these figures, it can be concluded that there is a negative relationship but not significant between inflation and unemployment in Indonesia in 1986 - 2016. For Okun legal compliance with the conditions of the Indonesian economy in 1986 to 2016, from data analysis obtained correlation coefficient of - 0.110 with a significance value of 0,556. From these figures, it can be concluded that there is a negative relationship but not significant between economic growth and unemployment in Indonesia in 1986-2016